Big five personality traits and motivation to learn Mandarin as foreign language - Ku, Chen Jung; Nurulasyikin Muda; Mohamad Rizal Abdul Hamid; Hanudin Amin; Suddin Lada; Anath Rau Krishnan (2019)
The study aims to develop a model explicating the role of student personality traits and motivation towards learning Mandarin as a foreign language. Data were collected using 50 undergraduates taking Mandarin language at Universiti Malaysia Sabah. We performed structural equation modelling (SEM) using SmartPLS 3.0 to test the research hypotheses. The path analysis revealed that the big five personality traits significantly influence and explained 52% of the variance in students’ motivation. Further, the analysis indicated that extraversion and conscientiousness produce the strongest correlation with students’ motivation. The results inferred that students who enjoy social visibility and self-discipline are also who will be motivated to learn Mandarin language. Findings also demonstrated that agreeableness positively influences motivation, and neuroticism produces negative direct relations with motivation towards learning Mandarin as a foreign language. On the contrary, the present study did not find any correlation between openness and motivation. The implications of this study are also discussed and interpreted within the context of what educators could do to encourage students’ motivation.